Systematic Approach to Agroforestry Policies and Practices in Asia - Park, M.S.; Baral, H.; Shin, S. (MDPI, 2022)
This paper introduces the Special Issue “Systematic Approach to Agroforestry Policies and Practices in Asia”. This Special Issue contains eleven papers on agroforestry at national, regional, and global levels. These papers discuss research trends; dominant services and functions of agroforestry; multiple case studies from Asian countries including Nepal, Lao PDR, Indonesia, Vietnam, Bangladesh, and Timor-Leste; and the benefits of agroforestry including income generation and carbon sequestration. They also interpret the goals, challenges, and social and cultural norms in agroforestry policies in national and local contexts. The research results can support policy design for the systematization and stabilization of agroforestry. This Special Issue provides us with scientific evidence and practical lessons on agroforestry policies and practices in Asia. It contributes to expanding the knowledge base for agroforestry and towards establishing and implementing agroforestry policies and practices in the region.